If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -8x = 144 + -36x Solving 6 + -8x = 144 + -36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36x' to each side of the equation. 6 + -8x + 36x = 144 + -36x + 36x Combine like terms: -8x + 36x = 28x 6 + 28x = 144 + -36x + 36x Combine like terms: -36x + 36x = 0 6 + 28x = 144 + 0 6 + 28x = 144 Add '-6' to each side of the equation. 6 + -6 + 28x = 144 + -6 Combine like terms: 6 + -6 = 0 0 + 28x = 144 + -6 28x = 144 + -6 Combine like terms: 144 + -6 = 138 28x = 138 Divide each side by '28'. x = 4.928571429 Simplifying x = 4.928571429
| -15+p+3=17 | | -7/3(-2.3333)-7 | | -2+1/4a-13 | | 1331-8x^3=0 | | 168=2w^2+10w+14 | | x+3.2-5.4=4.8 | | 3+4a=9-2a | | 6-9x=9x+21 | | 12(h-2)=-12 | | 5-3t=4t+19 | | 7(a+4)=-14 | | -7/3x-7 | | 4(x+2)-3x=15 | | 4x-4y=7-1 | | A=Q(1+rt) | | 18/7=54/x | | 5(a+1)=10a | | x+3.2-6.5=8.3 | | 4=2m-5m | | 9-4[3-2(3-5)]= | | 2-3x^25= | | 8/p+10=4/9 | | -5+7(X-2)=13X+5-6X | | 6m-7m=-3 | | 6x+20=7x+13 | | -10(-3b)=-180 | | V=Bak | | 40-11x=14x | | (5x-1)(2x+6)= | | 1.4q-4.3-5.2q=4.8q-3.8 | | -10(-36)=-180 | | 9t(2x)=2-(3x) |